A composite metal aluminum catalyst and its preparation method and application
The composite metal aluminum catalyst addresses the inefficiencies of existing methods by providing high conversion and selectivity with a flaky alumina structure and uniform active component distribution, resulting in efficient and cost-effective 3-methyl-2-butenol production.
Patent Information
- Application Number
- CN202310105774.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-13
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-02-13
AI Technical Summary
Existing methods for synthesizing 3-methyl-2-butenol face high reaction temperatures, long reaction times, catalyst deactivation due to coking, complex operations, and high costs associated with precious metal catalysts, leading to low selectivity and limited processing volumes.
A composite metal aluminum catalyst is prepared by dissolving a soluble aluminum salt with a nitric acid solution containing a noble metal and rare earth metal salt, forming spherical aluminum hydroxide gel, and calcining it to create a flaky alumina structure, ensuring uniform distribution of active components.
The catalyst achieves high conversion rates (>75%) and selectivity (>99%) at moderate temperatures (30-45°C) with a long catalyst life (>1 year), reducing production costs and maintaining high yield and selectivity.
Smart Images

Figure CN116272978B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of isopentenol production, and specifically relates to the preparation and application of a composite metal aluminum catalyst. Background Art
[0002] 3-Methyl-2-butenol, also known as isopentenol, can be used as a fragrance and can also be used to prepare other chemical products, such as citral, isophytol, DV chrysanthemic acid methyl ester, etc. 3-Methyl-2-butenol can be prepared by the transposition reaction of 3-methyl-3-butene-1-ol.
[0003] The reaction of 3-methyl-3-butene-1-ol to generate 3-methyl-2-butenol can be a gas phase reaction or a liquid phase reaction, and a wide variety of catalysts can be used. In the gas phase reaction, oxides of group IA or IA elements are often used as active components, such as strong bases such as CsOH, CH3ONa, KOH, and NaOH as catalysts. For example, MgO is used as a catalyst in a prenol preparation technology disclosed in JP0826893, the reaction temperature is 150-300°C, the reaction time is 3h, the conversion rate reaches 57%, and the selectivity is 99%.
[0004] Most of the liquid phase reactions use metals or metal complexes of the eighth group as active components, such as carbonyl iron. CN107141197 discloses a method for preparing isopentenol, which uses carbonyl iron, an organic base and an epoxy ligand as catalysts. In an atmosphere of CO and N2, the reaction solution is diluted with an ether substance, and reacts in a reactor at 0.5 MPa and 80°C for 2 hours. The reaction conversion rate is 47.3% and the selectivity is 98.8%. Metals such as Pt, Pd, Rh, and Ir have been reported. Yoshimura Noriak used a fluidized bed reactor to study the optimization evaluation of using precious metals Pt, Pd, and Ru as active centers, Cd, Sn, P, and S as additives, and SiO2 as a carrier. Under the optimal conditions, the raw material conversion rate is 50% and the isopentenol selectivity is more than 90%. W02008037693 reported a heterogeneous supported precious metal catalyst whose active components are Pd, Se and Te, with carbon as the carrier and xylene as the solvent. The reaction was carried out at 80°C in a glass kettle for 4.5 hours, with a conversion rate of 63.4% and a selectivity of 84.5%.
[0005] The existing technologies for synthesizing 3-methyl-2-butenol generally have the following problems: the temperature of gas phase isomerization reaction is high, the reaction time is long, it is easy to coke during the reaction process, resulting in catalyst deactivation, and it is basically an intermittent reaction, with a small processing volume and complicated operation; the liquid phase reaction uses metal carbonyl compounds and organic bases, which makes the subsequent separation process complicated, and the reaction liquid is diluted with ethers, resulting in limited processing volume. At the same time, the catalyst has poor selectivity and many by-products. Most of the technologies reported to use precious metal catalysts use intermittent operation, and the number of intermittent reactions is small, and the catalyst cost is high. The continuous process uses more complex processes such as fluidized beds, and the catalyst life used in the continuous process is short, and the equipment investment is high. Summary of the invention
[0006] The present invention provides a composite metal aluminum catalyst and a preparation method and application thereof. When the composite metal aluminum catalyst is used for the hydroisomerization reaction of 3-methyl-3-butene-1-ol, the conversion rate and selectivity are high and the reaction conditions are mild, thus solving the problems of low catalyst activity, small unit processing volume, short catalyst life and easy loss of active components in the prior art.
[0007] The technical solution of the present invention is as follows:
[0008] A method for preparing a composite metal aluminum catalyst comprises:
[0009] (1) dissolving a soluble aluminum salt in water and stirring the mixture, then adding a nitric acid solution containing a template, and simultaneously adding a nitric acid solution containing a noble metal salt and a rare earth metal salt, and then heating and refluxing and stirring the mixture to obtain an alumina sol containing an active component;
[0010] The precious metal contained in the precious metal salt is one or more of Ru (ruthenium), Pd (palladium), Rh (rhodium), Ir (iridium) and Pt (platinum);
[0011] The rare earth metal contained in the rare earth metal salt is one or more of La (lanthanum), Ce (cerium), Pr (praseodymium), Nd (neodymium), Pm (promethium) and Sm (samarium);
[0012] (2) dropping the alumina sol obtained in step (1) into a preformed oil-ammonia water two-phase system, the sol droplets pass through the oil layer, and then form spherical aluminum hydroxide gel in the ammonia water layer and age;
[0013] (3) The spherical aluminum hydroxide gel after aging in step (2) is sequentially washed with water, washed with alcohol and dried to obtain aluminum oxide particles containing active components, and then calcined and reduced to obtain the composite metal aluminum catalyst.
[0014] The present invention adopts a special molding method to obtain flaky alumina crystals instead of conventional spherical stacking. The flaky stacking form of the crystals significantly improves the performance of the catalyst. At the same time, the introduction of active components and additives is completed before the alumina is molded, which significantly improves the distribution of the active components and additives on the catalyst surface.
[0015] Preferably, in step (1), the soluble aluminum salt is one of aluminum nitrate, aluminum isopropoxide, and aluminum chloride, and more preferably aluminum isopropoxide.
[0016] Preferably, in step (1), the template is one of P123, MCM-41, MCM-48, and KIT-1.
[0017] Preferably, in step (1), the noble metal salt is a noble metal nitrate, and the noble metal is Pd or Pt;
[0018] The rare earth metal salt is rare earth metal nitrate, and the rare earth metal is La or Ce.
[0019] Preferably, in step (1), the molar ratio of the noble metal salt to the rare earth metal salt is 4 to 21:1;
[0020] The mass ratio of the soluble aluminum salt to the template is 15 to 35:1;
[0021] The molar ratio of the soluble aluminum salt to the noble metal salt is 200-500:1.
[0022] Preferably, in step (1), the stirring temperature of the soluble aluminum salt is 60 to 80° C., and the stirring time is 4 to 12 hours.
[0023] Preferably, in step (2), the oil contained in the oil-ammonia water two-phase system is one of n-hexane, cyclohexane, toluene and petroleum ether;
[0024] The concentration of the ammonia water is 5 to 15 wt.%;
[0025] The oil layer in the oil-ammonia water two-phase system has a height of 3 to 8 cm, and the water layer has a height of 3 to 8 cm;
[0026] The addition rate of the alumina sol is 0.5 to 1.5 mL / min, more preferably 0.5 to 1.2 mL / min.
[0027] In step (2), the aging time is 1 to 12 hours.
[0028] In step (3), the solvent used for alcohol washing is methanol.
[0029] In step (3), the calcination temperature is 800-1000°C and the calcination time is 3-12 hours.
[0030] In step (3), the reduction temperature is 200 to 400° C., and the reduction time is 2 to 12 hours.
[0031] The present invention also provides a composite metal aluminum catalyst obtained by the above preparation method.
[0032] Preferably, the composite metal aluminum catalyst is a sheet-like stacked structure.
[0033] Preferably, the precious metal content is 0.5-1% by mass, and more preferably, the rare earth metal content is 0.05%-0.2%, wherein the content is calculated as the ratio of the precious metal to the carrier, the carrier is aluminum oxide, and the precious metal is measured as a metal element.
[0034] The present invention also provides a method for preparing 3-methyl-2-butenol, comprising:
[0035] Under the action of the composite metal aluminum catalyst, 3-methyl-3-butene-1-ol undergoes a hydroisomerization reaction to obtain the 3-methyl-2-butenol.
[0036] Preferably, the composite metal aluminum catalyst is loaded in a bubbling bed reactor, and the hydroisomerization reaction is continuously carried out in the bubbling bed reactor;
[0037] The temperature of the hydroisomerization reaction is 30-45°C, and the residence time of the raw materials is 0.5-2h -1 .
[0038] Preferably, the flow rate of the 3-methyl-3-butene-1-ol is 0.5 to 20 mL / min, and the flow rate of the hydrogen is 5 to 20 mL / min.
[0039] By using the catalyst provided by the present invention to carry out the reaction, the conversion rate of the raw material 3-methyl-3-butene-1-ol is higher than 75%, the selectivity of the product 3-methyl-2-butene-1-ol is higher than 99%, and the total yield of the product after separation is greater than 74%. After separation, the 3-methyl-3-butene-1-ol can be recycled to the raw material storage tank for further reaction. The catalyst has high activity. In low response At a medium temperature (30-45°C), high selectivity and yield can still be maintained ,at the same time The service life of the catalyst can reach more than 1 year The used catalyst was tested by ICP and BET, and the precious metal active components were not lost, and the pore structure of the catalyst carrier did not change significantly, which greatly reduced the production cost and had a high application value.
[0040] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0041] (1) The catalyst is prepared using a one-pot method, where the active components and auxiliary components are added and mixed at the aluminum hydroxide sol stage. This method greatly improves the uniformity of the distribution of the active components and auxiliary components inside and outside the carrier. Compared with the conventional impregnation method, this method is not affected by the adsorption capacity of the carrier itself, and can completely load the added components on the carrier. And thanks to the high dispersion of the active components, the catalyst showed extremely high activity in the evaluation of the 3-methyl-3-butene-1-ol transposition reaction.
[0042] (2) This method uses a special molding method, and the crystals of the alumina carrier of the prepared catalyst are stacked in flakes. This stacking method is more conducive to promoting the interaction between the carrier and the additives and active components, thereby improving the activity and selectivity of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 is a SEM scan of catalyst 1 obtained in Example 1;
[0044] Figure 2 This is a SEM scan of the catalyst 2* obtained in Comparative Example 2;
[0045] Figure 3 Is the gas chromatogram of the raw material 3-methyl-2-butenol;
[0046] Figure 4 This is a gas chromatogram showing the evaluation results of Catalyst 1 of Application Example 1. DETAILED DESCRIPTION
[0047] Catalyst Preparation Example 1
[0048] (1) Preparation of sol: 40 g of aluminum isopropoxide and 120 mL of deionized water were placed in a three-necked flask. A condenser was installed on the three-necked flask, and the container was placed in a water bath at 80° C. for constant temperature reflux and stirring for 4 h. After 4 h, 25 mL of 1.5 mol / L nitric acid solution and 20 mL of 0.1 g / mL P123 template solution prepared in advance were added to the system while maintaining the temperature at 80° C. At the same time, a mixed solution containing 0.17 g of palladium nitrate, 0.02 g of lanthanum nitrate and 5 mL of 5% dilute nitric acid was added. After all the additions were completed, the water bath temperature was raised to 95° C. and constant temperature reflux and stirring were continued for 6 h. After the stirring was completed, a stable alumina / active component sol was obtained.
[0049] (2) Preparation of spherical gel
[0050] 10wt.% ammonia water was prepared in advance and placed in a cylindrical wide-mouth container, and oil (n-hexane) was added thereto to form an oil-ammonia water biphase in the container, wherein the oil layer height was 5cm and the water layer height was 5cm. After the preparation was completed, a needle (model 18G) was installed at the outlet of the peristaltic pump pipeline, and then the peristaltic pump was used to drip the sol at a uniform rate of 1mL / min, so that the sol droplets passed through the oil layer at a uniform speed and formed spherical aluminum hydroxide gel in the ammonia water layer. After all the sols were dripped, the aluminum hydroxide gel particles were placed in ammonia water for aging for 1h.
[0051] (3) Washing and drying
[0052] After aging, use a sand core funnel to transfer the aluminum hydroxide gel from the ammonia water to another container. At this time, about 15g of aluminum hydroxide spherical particles are taken out. First, take 100mL of deionized water to wash the aluminum hydroxide gel. Each washing must completely immerse the sol particles. After standing for 0.5h, pour out the washing liquid and repeat this step until the pH value of the washing liquid is neutral. Then take 100mL of methanol to soak the aluminum hydroxide gel particles for 0.5h. Repeat three times to replace the water adsorbed by the gel particles. Transfer the washed gel to a watch glass and dry it at 120℃ for 12h.
[0053] (4) Calcination
[0054] After drying, the alumina particles were taken out, transferred to a porcelain boat, and placed in a muffle furnace for calcination. The calcination temperature program was as follows: heating to 500°C at 5°C / min, maintaining at 500°C for 4 hours, heating to 900°C at 5°C / min, maintaining at 900°C for 6 hours, then the insulation was terminated and the alumina was taken out after the temperature of the muffle furnace dropped to room temperature.
[0055] (5) Catalyst reduction
[0056] After taking out the alumina, it was transferred into a quartz tube furnace, and nitrogen was turned on to purge and replace the air in the tube furnace. The nitrogen gas flow rate was 100 mL / min, and the purge was 0.5 h. After the purge was completed, the nitrogen was turned off, and hydrogen was turned on for purge. The hydrogen flow rate was 100 mL / min, and the purge was 0.5 h. After the hydrogen replacement was completed, the hydrogen gas rate was increased to 300 mL / min, and the heating program of the tube furnace was started at the same time. The specific program was: 5 ° C / min was heated to 300 ° C, and maintained at 300 ° C for 3 h. After the insulation was completed, the hydrogen was turned off and replaced with nitrogen. The nitrogen gas flow rate was 100 mL / min, and the purge was 0.5 h. After the purge was completed, the catalyst could be taken out after waiting for the temperature of the tube furnace to drop to room temperature, which was recorded as catalyst 1. From the electron microscope scanning of catalyst 1, it can be seen that the alumina crystals prepared by this method are flaky accumulation.
[0057] Catalyst Preparation Examples 2 to 12
[0058] By changing the aluminum source, the type of rare earth metal and precious metal, and the loading amount of rare earth metal and precious metal, the following catalysts were prepared according to the method of Example 1:
[0059] Table 1 Catalyst models and preparation parameters
[0060]
[0061]
[0062] Catalyst Preparation Comparative Example 1
[0063] Preparation of Catalyst 1*:
[0064] (1) Preparation of impregnation solution: Take 35 g of purified water, add 30.8 g of Ce(NO3), 40 mL of 0.02 g / mL chloropalladic acid solution, and stir for 0.5 h;
[0065] (2) Impregnation of active components and additives: Take 100 g of spherical commercial γ-alumina and place it in the prepared impregnation solution for 3 h;
[0066] (3) Drying and calcination: The impregnated catalyst was placed in a forced air drying oven and dried at 120°C for 4 h. After drying, it was placed in a muffle furnace and calcined at 500°C for 6 h.
[0067] (4) Reduction: After taking out the alumina, transfer it into a quartz tube furnace, start nitrogen to purge and replace the air in the tube furnace, the nitrogen flow rate is 100 ml / min, purge for 0.5 h, after the purge is completed, turn off the nitrogen, turn on hydrogen to purge, the hydrogen flow rate is 100 ml / min, purge for 0.5 h, after the hydrogen replacement is completed, increase the hydrogen flow rate to 300 ml / min, and start the heating program of the tube furnace body at the same time. The specific program is: increase the temperature to 300°C at 5°C / min, maintain 300°C for 3h, after the insulation is completed, turn off the hydrogen and replace it with nitrogen, the nitrogen flow rate is 100 ml / min, purge for 0.5h, after the purge is completed, wait for the temperature of the tube furnace body to drop to room temperature and then take out the catalyst, which is recorded as catalyst 1*.
[0068] Catalyst Preparation Comparative Example 2*
[0069] Preparation of catalyst 2*:
[0070] (1) Preparation of sol: 40 g of aluminum isopropoxide and 120 mL of ethanol were placed in a three-necked flask, a condenser was installed on the three-necked flask, and the container was placed in a water bath at 80° C. for constant temperature reflux stirring for 4 h. After 4 h, 25 mL of 1.5 mol / L nitric acid solution and 20 mL of 0.1 g / mL P123 template solution prepared in advance were added to the system, and a mixed solution containing 0.17 g of palladium nitrate, 0.03 g of lanthanum nitrate and 5 mL of 5% dilute nitric acid was added at the same time. After all the additions were completed, the water bath temperature was raised to 95° C. and constant temperature reflux stirring was continued for 6 h. After the stirring was completed, a stable alumina / active component sol was obtained;
[0071] (2) Removing the solvent: The prepared precursor / anhydrous ethanol mixture was transferred into a rotary evaporator, the rotation speed was maintained at 60 rpm, the water bath temperature was 60°C, and the vacuum degree was 0.1 MPa, and the anhydrous ethanol in the mixture was dried;
[0072] (3) Drying and calcination: The dried catalyst block was placed in a forced air drying oven and dried at 120°C for 4 h. After drying, the catalyst was placed in a muffle furnace and heated to 800°C at a rate of 5°C / min and calcined for 4 h.
[0073] (4) Reduction of the catalyst: After taking out the alumina, transfer it into a quartz tube furnace, start nitrogen to purge and replace the air in the tube furnace, the nitrogen flow rate is 100 mL / min, purge for 0.5 h, after the purge is completed, turn off the nitrogen, turn on hydrogen to purge, the hydrogen flow rate is 100 mL / min, purge for 0.5 h, after the hydrogen replacement is completed, increase the hydrogen flow rate to 300 mL / min, and start the heating program of the tube furnace at the same time. The specific program is: increase the temperature to 300 °C at 5 °C / min, maintain 300 °C for 3 h, after the insulation is completed, turn off the hydrogen and replace it with nitrogen, the nitrogen flow rate is 100 mL / min, purge for 0.5 h, after the purge is completed, wait for the temperature of the tube furnace to drop to room temperature before taking out the catalyst, which is recorded as catalyst 2*. Figure 2 is the electron microscope scanning image of the prepared catalyst 2*. Figure 2 It can be seen that the alumina crystals prepared by this method are spherical stacks.
[0074] Catalyst Preparation Comparative Example 3
[0075] The preparation method of catalyst 3* is the same as the process of catalyst preparation example 1, except that 0.14g H[AuCl4] is used instead of 0.17g palladium nitrate.
[0076] Among them, Preparation Example 1 is a catalyst prepared by conventional impregnation method, Preparation Example 2 is a catalyst prepared by one-pot method using anhydrous ethanol as solvent, and Preparation Example 3 is the same as the preparation process of Example 1, with Au replacing Pd as the precious metal component.
[0077] The catalytic activity of the catalyst is further evaluated by applying examples.
[0078] Application Example 1
[0079] The catalyst evaluation device consists of a raw material storage tank, a bubbling bed reactor, a reaction liquid storage tank, a plunger pump, a solenoid valve, a pressure reducing valve and a gas cylinder.
[0080] The catalyst was activated before use. After activation, 100 g of catalyst 1 was added to a trickle bed reactor with an inner diameter of 10 mm and a length of 50 cm. The catalyst particle size was 3 mm. The filling started from the bottom of the reaction tube. The filling height was 45 cm and the filling density was 0.7 g / cm 3 After loading, the fixed bed reactor was heated to 40°C and purged with N2 for 4 hours at a purge rate of 300 mL / min. The raw material 3-methyl-3-butene-1-ol and hydrogen were continuously introduced into the bubbling bed reactor containing the catalyst from the bottom of the reactor. The reaction temperature was 45°C and the space velocity was 1.0 h -1 The reaction was carried out under the condition that the volume flow rate ratio of the raw material to the hydrogen was 2:1. The liquid product was analyzed by gas chromatography. The conversion rate was 75.3% and the selectivity was 99.1%. The results are shown in Table 2.
[0081] Among them, the gas chromatogram of the raw material 3-methyl-2-butenol is shown in Figure 3 The gas chromatogram of the evaluation results is shown in Figure 4 .
[0082] Gas chromatography detection conditions: gas chromatography column Agilent DB-17 (30m*320um*0.25um), gas chromatograph Agilent 7820A.
[0083] The injection volume was 0.2ul, the injection port temperature was 240°C, the split ratio was 150:1, and the split flow rate was 150mL / min.
[0084] The column box temperature was maintained at 70°C for 10 min.
[0085] The detector temperature was 240°C, the hydrogen flow rate was 30 mL / min, the air flow rate was 400 mL / min, and the tail gas flow rate was 25 mL / min.
[0086] The catalyst was run for a long period of time. After 7200 hours, the conversion rate was 75-76%, the selectivity was more than 99%, and the purity of the product isopentenol was 99.5-99.6%, that is, the catalyst had excellent stability.
[0087] Application Examples 2 to 15
[0088] Preparation Examples 2 to 12 and Comparative Preparation Examples 1 to 3 were subjected to catalyst effect evaluation in the same manner as in Example 1. The specific evaluation results are shown in Table 2:
[0089] Table 2 Summary of evaluation results of each catalyst
[0090] Catalyst type Raw material conversion rate / % Product selectivity / % Yield / % Example 1 Catalyst 1 75.1 99.2 74.5 Example 2 Catalyst 2 74.3 99.1 73.6 Example 3 Catalyst 3 74.0 99.1 73.3 Example 4 Catalyst 4 74.5 98.9 73.7 Example 5 Catalyst 5 74.1 99.2 73.5 Example 6 Catalyst 6 75.0 99.1 74.3 Example 7 Catalyst 7 74.6 98.8 73.7 Example 8 Catalyst 8 74.5 99.0 73.8 Example 9 Catalyst 9 74.0 97.0 71.8 Example 10 Catalyst 10 72.9 97.2 70.9 Embodiment 11 Catalyst 11 70.5 98.9 69.7 Example 12 Catalyst 12 74.6 98.8 73.7 Comparative Example 1 Catalyst 1* 69.3 96.1 66.6 Comparative Example 2 Catalyst 2* 55.8 95.9 53.5 Comparative Example 3 Catalyst 3* 61.0 97.0 58.3
[0091] Catalyst life evaluation experiment
[0092] The catalyst 1 prepared in Example 1 was subjected to long cycle life and high space velocity evaluations. The results are shown in Tables 3 and 4.
[0093] Table 3 Catalyst long-term evaluation results
[0094]
[0095]
[0096] Table 4 Catalyst high space velocity evaluation results
[0097]
[0098] As shown in Tables 3 and 4, the performance of the catalyst did not change significantly during the 7200 h evaluation, the conversion of 3-methyl-3-butene-1-ol was maintained at 75%, and the selectivity of 3-methyl-2-butenol was maintained at more than 99%. -1 The catalyst was evaluated at an extremely high air velocity of 10.5 h -1 The catalyst conversion rate was 74.5% and the selectivity remained at 99.0%.
[0099] After the long-term evaluation, the catalyst 1 was removed from the reactor, and the residual reaction liquid was dried and then subjected to ICP and BET tests. The results are shown in Tables 5 and 6.
[0100] Table 5 Comparison of changes in components before and after long-term evaluation of catalyst (ICP test)
[0101]
[0102]
[0103] Table 6 Comparison of pore data before and after long-term evaluation of catalyst (BET test)
[0104] Evaluation time Average pore size / nm <![CDATA[Specific surface area / m 2 *g-1]]> Total pore volume / cc*g-1 Before use 5.16 460.44 1.05 After running for 1500h 5.36 456.40 1.02
[0105] The results in Tables 5 and 6 show that after long-term reaction, the pore data and components of the catalysts maintain a high stability.
Claims
1. A method for preparing a composite metal aluminum catalyst, characterized in that: include: (1) dissolving a soluble aluminum salt in water and stirring the mixture, then adding a nitric acid solution containing a template, and simultaneously adding a nitric acid solution containing a noble metal salt and a rare earth metal salt, and then heating and refluxing and stirring the mixture to obtain an alumina sol containing an active component; The precious metal contained in the precious metal salt is one of the elements Ru, Pd, Rh, Ir, and Pt; The rare earth metal contained in the rare earth metal salt is one of La, Ce, Pr, Nd, Pm, and Sm elements; (2) dropping the alumina sol obtained in step (1) into a preformed oil-ammonia water two-phase system, wherein the alumina sol droplets pass through the oil layer, and then form spherical aluminum hydroxide gel in the ammonia water layer and age; (3) The spherical aluminum hydroxide gel aged in step (2) is sequentially washed with water, washed with alcohol and dried to obtain aluminum oxide particles containing active components, and then calcined and reduced to obtain the composite metal aluminum catalyst; The composite metal aluminum catalyst is a sheet-like stacked structure; In terms of mass percentage, the content of precious metal elements is 0.5~1%, and the content of rare earth metal elements is 0.05%~0.2%.
2. The method for preparing the composite metal aluminum catalyst according to claim 1, characterized in that: In step (1), the soluble aluminum salt is one of aluminum nitrate, aluminum isopropoxide, and aluminum chloride.
3. The method for preparing the composite metal aluminum catalyst according to claim 1, characterized in that: In step (1), the template is P123.
4. The method for preparing the composite metal aluminum catalyst according to claim 1, characterized in that: In step (1), the noble metal salt is a noble metal nitrate; The rare earth metal salt is rare earth metal nitrate.
5. The method for preparing the composite metal aluminum catalyst according to claim 1, characterized in that: In step (1), the molar ratio of the noble metal salt to the rare earth metal salt is 4-21:1; The mass ratio of the soluble aluminum salt to the template is 15-35:1; The molar ratio of the soluble aluminum salt to the noble metal salt is 200-500:
1.
6. The method for preparing a composite metal aluminum catalyst according to claim 1, characterized in that: In step (1), the stirring temperature of the soluble aluminum salt is 60-80° C., and the stirring time is 4-12 h.
7. The method for preparing a composite metal aluminum catalyst according to claim 1, characterized in that: In step (2), the oil contained in the oil-ammonia water two-phase system is one of n-hexane, cyclohexane, toluene and petroleum ether; The concentration of the ammonia water is 5-15wt.%; The oil layer in the oil-ammonia water two-phase system has a height of 3-8 cm and a water layer has a height of 3-8 cm; The addition rate of alumina sol is 0.5~1.2mL / min.
8. A method for preparing 3-methyl-2-butenol, characterized in that: include: Under the action of the composite metal aluminum catalyst obtained by the preparation method according to any one of claims 1 to 7, 3-methyl-3-butene-1-ol undergoes a hydroisomerization reaction to obtain the 3-methyl-2-butenol.
9. The method for preparing 3-methyl-2-butenol according to claim 8, characterized in that: The composite metal aluminum catalyst is loaded in a bubbling bed reactor, and the hydroisomerization reaction is continuously carried out in the bubbling bed reactor; The temperature of the hydroisomerization reaction is 30-45°C, and the residence time of the raw materials is 0.5-2h -1 .
10. The method for preparing 3-methyl-2-butenol according to claim 8, characterized in that: The flow rate of the 3-methyl-3-butene-1-ol is 0.5-20 mL / min, and the flow rate of the hydrogen is 5-20 mL / min.
Citation Information
Patent Citations
Formation of oxide superconducting thin film with c-axis in-plane orientation and a-axis orientation and base body therefor
JP1996026893A
O-phenyl phenol preparation catalyst by cyclohexanone dimer dehydrogenation and preparation method thereof
CN101455962A
Preparation method of mesoporous Al 2O3 loading nano Pd (palladium) catalyst
CN105478109A
